Um olhar investigativo para a metodologia de projetos em uma escola pública estadual: na busca da qualificação do ensino de ciências e biologia - Bozzato, Carla Vargas (2013)
Investigate Project Methodology as a strategy for teaching qualification and teaching of Science and Biology in a public school is the goal of this research. The investigation was conducted with teachers, students of the school year of 2013 and graduated from the period 2010 to 2012 the High School of the Technical School Professor Sylvia Mello-RS and participating in educational projects within these areas. This qualitative study used as the case study methodology of type Ethnographic and followed the line of thought ecosystem, characterized as constructivist, interactionist, sociocultural, emotional and transcendent proposed by Maria Candida Moraes (2008) supported the assumptions mentioned by Maturana ( 2001). The data collection instruments were: observations of the development of education projects forwarded to supervision in the period August to December 2012, document analysis, interviews and questionnaires. The discursive textual analysis followed the guidelines de Moraes&Galiazzi (2011), with the intention of seeking the understanding and reconstruction of existing knowledge about school quality, design methodology and teacher training. The results indicate the need for the school to innovate in order to think of strategies that take the student to be a protagonist of their processes of teaching and learning, increase opportunities for learning in a work related research and enhancement of the use of the methodology projects to provide an active character education, constructive, affective, and relational dynamics respecting history and the environment in which it is inserted realize they must take a stance with this of belonging, commitment and responsibility. Towards the teacher, we also realize the need to think about their role within the school of contemporaneity, the need to be search engine of their own practice, to realize the student is also a chance for the collective construction of knowledge, dialogue with peers, to seek and allow change and constant teaching qualification.